Survivability of bare, individual Bacillus subtilis spores to high-velocity surface impact: Implications for microbial transfer through space. (June 2016) - Barney, Brandon L.; Pratt, Sara N.; Austin, Daniel E.
Abstract: Laboratory experiments show that endospores of Bacillus subtilis survive impact against a solid surface at velocities as high as 299 ± 28 m/s. During impact, spores experience and survive accelerations of at least 10 10  m/s 2 . The spores were introduced into a vacuum chamber using an electrospray source and accelerated to a narrow velocity distribution by entrainment in a differentially pumped gas flow. Different velocity ranges were studied by modifying the gas flow parameters. The spores were electrically charged, allowing direct measurement of the velocity of each spore as it passed through an image charge detector prior to surface impact. Spores impacted a glass surface and were collected for subsequent analysis by culturing. Most spores survived impact at all measured velocities. These experiments differ fundamentally from other studies that show either shock or impact survivability of bacteria embedded within or on the surface of a projectile. Bacteria in the present experiments undergo a single interaction with a solid surface at the full impact velocity, in the absence of any other effects such as cushioning due to microbe agglomerations, deceleration due to air or vapor, or transfer of impact shock through solid or liquid media. During these full-velocity impact events, the spores experience extremely high decelerations. This study is the first reported instance of accelerations of this magnitude experienced during a bacteria impact event. These results are discussed in the context of potential transfer of viable microbes in space and other scenarios involving surface impacts at high velocities. Highlights: Individual bacterial spores survive surface impact up to 299 m/s. Locally well-defined impact parameters compared to other impact and shock experiments. Implications for microbial transfer through space discussed.